Analisis Pengaruh Promosi dan Kualitas Pelayanan pada Lembaga Keuangan Syariah Terhadap Minat Menabung Karyawan PT. SAMI-JF - Eki Dwi Septiani; Miswan Ansori; Zahrotun Nafisah (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
Islamic Financial Institutions are institutions that have a large role in the growth of the country, but in reality the interest in saving in Islamic Financial Institutions is still relatively low. This study aims to analyze the effect of promotion and service quality on interest in saving in Islamic Financial Institutions. The method used in this study is quantitative. The study was conducted at PT. SAMI-JF Jepara in June 2024 with 130 respondent samples. Data collection was carried out by distributing questionnaires to the research sample. Data analysis was carried out using multiple linear regression techniques with the help of SPSS software. The results of the study show that partially the promotion variable affects the variable of interest in saving, partially the variable of service quality affects the variable of interest in saving and simultaneously the promotion variable and the variable of service quality affect the variable of interest in saving. This study has a role in formulating the right formula to increase interest in saving in Islamic Financial Institutions so that they are not less prestigious than Conventional Financial Institutions.